2014
DOI: 10.1097/brs.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparative Study of 2 Minimally Invasive Decompression Procedures for Lumbar Spinal Canal Stenosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 24 publications
4
26
0
1
Order By: Relevance
“…Moreover, the duration of hospital stay was significantly shorter in the unilateral laminotomy group. We excluded eight studies because the control group did not meet the criteria of this review [6,[41][42][43][44][45][46][47]. We excluded three studies because the design precluded a reliable comparison of decompression techniques [48][49][50].…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Moreover, the duration of hospital stay was significantly shorter in the unilateral laminotomy group. We excluded eight studies because the control group did not meet the criteria of this review [6,[41][42][43][44][45][46][47]. We excluded three studies because the design precluded a reliable comparison of decompression techniques [48][49][50].…”
Section: Excluded Studiesmentioning
confidence: 99%
“…It has been reported the usefulness of both procedures to treat patients with single level spinal stenosis [11]. In a recent prospective study, in patients with multilevel decompression, UBLD was found superior to MILD in term of low back pain and lumbar function (increased sagittal translation and lumbar lordosis in MILD compared to UBLD, probably due to the removal of half of the spinous processes in the MILD) [10]. Nonetheless, Mobbs et al [12] reported that UBLD can have some disadvantages such as the difficulty of manipulating instruments through a small portal (resulting in a more significant dural sac retraction and a higher possibility of dural tears) and the higher recurrence and reoperation rates due to minimal exposure, leading to inadequate decompression [12].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that fusion may increase the biomechanical stress imposed on the adjacent segments, leading to overload disease [18] and requiring secondary spine surgery for lumbar adjacent instability [19]. To overcome these problems, minimal invasive procedures have been reported in the literature [10]- [14]. The most common minimal invasive approaches are: the muscle-preserving interlaminar decompression (MILD), introduced by Hatta et al [8] and the unilateral approach for bilateral decompression (ULBD), reported by Spetzger et al [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations